Prudent Use of Antibiotics in Dairy Cows: The Nordic Approach to Udder Health - Rajala-Schultz, Päivi; Nødtvedt, Ane; Halasa, Tariq; Persson Waller, Karin (Frontiers in Veterinary Science, 2021)
Global concerns regarding bacterial antibiotic resistance demand prudent use of antibiotics in livestock, including dairy, production. Dairy production in the Nordic countries has a low consumption of antibiotics, while animal health, productivity and milk quality are at high levels. Here, we describe the basis of Nordic mastitis control and treatment strategies, as a model for production of high-quality milk with prudent use of antibiotics. We hope this will be beneficial for dairy producers and advisors in other countries and regions that consider limiting antibiotic use in cattle herds. In this perspectives paper we describe the dairy sector in the Nordic countries, and present regulatory aspects of antibiotic use, diagnostics and current guidelines for treatment of clinical mastitis as well as dry cow therapy. We also show summary statistics of udder health indicators in Denmark, Finland, Norway and Sweden, to illustrate the effects of the implemented udder health management practices.